2015
DOI: 10.1016/j.sjpain.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

I see you’re in pain – The effects of partner validation on emotions in people with chronic pain

Abstract: Background and aims Chronic pain not only affects the person in pain, but can also have a negative impact on relationships with loved ones. Research shows that chronic pain is associated with difficulties in marital relationships, which in turn is related to a variety of negative outcomes such as psychological distress and conflict within the family. This suggests that couples where chronic physical pain is present also struggle with emotional pain and relationship problems, and thus targeting relationship ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 33 publications
2
39
0
1
Order By: Relevance
“…In line with the model, validation training was in a recent study found to increase the frequency of validating responses while decreasing invalidating responses, and this had a positive effect on emotions in the person with pain [2]. Further, a significant association was in another study found between invalidation from the partner and pain disability [37].…”
Section: Research Findings the Significance Of Affective Interactionmentioning
confidence: 66%
See 2 more Smart Citations
“…In line with the model, validation training was in a recent study found to increase the frequency of validating responses while decreasing invalidating responses, and this had a positive effect on emotions in the person with pain [2]. Further, a significant association was in another study found between invalidation from the partner and pain disability [37].…”
Section: Research Findings the Significance Of Affective Interactionmentioning
confidence: 66%
“…A few studies on validating and invalidating partner responses have recently been presented. Findings indicate that validation is associated with decreases in negative affect [2] and that invalidation is associated with higher pain disability [37]. As it leads to opposite predictions from those of the operant model when it comes to the effect of negative/invalidating partner responses, the model might explain some of the mixed results observed within the operant framework.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This study adds to the growing body of literature which implicates the value of validation in the context of chronic pain; validating feedback (or at least lack of invalidating feedback) has been found to increase emotional wellbeing [4], reduce physiological arousal [5,6], increase pain tolerance and adherence [7], reduce ratings of pain intensity and frustration [8] and counteract the interference caused by pain catastrophizing on individuals' ability to recall information [9] compared with invalidating feedback. Thus, communicating understanding and acceptance in the context of pain, may have worthwhile and far-reaching consequences.…”
Section: High Validation and Low Invalidation Important For Outcome Omentioning
confidence: 86%
“…Further research is needed on how to implement such elements in psychological treatment; there are examples in the literature of psychological interventions that include training in validation for partners [55,56]. Similar interventions have been implemented in medical contexts, in which people who were suffering from medical conditions such as long-term pain showed more favorable emotional outcomes when their partners received training in validation [57]. Hence, training partners in emotional communication and possibly implementing communication training to an extended social network and even medical professionals might be helpful for infertile women and might influence their sense of social support.…”
Section: Discussionmentioning
confidence: 99%